Pregnant Women’s Knowledge of Chronic Energy Deficiency with Economic Status - Rindasari Munir; Sunarti (AbdimasMu UMTAS, 2022)
One of the causes of maternal and child mortality is poor nutritional status and low nutritional intake of pregnant women during pregnancy so that it can cause health problems for mothers and babies. The purpose of this community service is to increase the knowledge of pregnant women about Chronic Energy Deficiency as an effort to prevent both short and long term. This community service was carried out in March 2022. Community service activities focused on increasing awareness of pregnant women in fulfilling nutrition during pregnancy so that chronic energy deficiency did not occur. Pregnant women do a pre-test before being given counseling with the aim of knowing the description of pregnant women's knowledge about chronic energy deficiency. Counseling is carried out directly, after being given counseling, pregnant women return to doing a post-test with the aim of knowing the picture of the community after being given counselling. The results obtained after being given counseling on knowledge of pregnant women about chronic energy deficiency increased, and there was a significant relationship between knowledge of pregnant women about chronic energy deficiency and economic status. This activity went well and pregnant women were very enthusiastic.